Demographic Factors and Disease Patterns in Surkhandarya Region: Implications for Population Health: Faktor Demografi dan Pola Penyakit di Wilayah Surkhandarya: Implikasi terhadap Kesehatan Penduduk - Gulshoda , Narmanova (Indonesian Journal of Innovation Studies, 2023)
This study aims to examine the role of demographic factors in the structural and territorial formation of labor resources and changes in the age and sex structure of the population in Surkhandarya region, Uzbekistan. The analysis includes an assessment of the most common diseases observed in the region's population and their implications for population health. Data from Table 2.2 reveal a shift in the proportion of men and women over the last decade, with men gaining the upper hand in recent years. The birth rate is influenced by various factors, including natural-biological, demographic, socio-economic, cultural, and educational levels. The Surkhan oasis, as an ancient inhabited area, has unique population dynamics and attitudes towards the birth process. Mortality rates varied across cities and districts, with a higher incidence observed in diseases related to the circulatory and respiratory systems. The findings underscore the high demographic potential and health challenges faced by the Surkhandarya region. In January-March 2023, there were 3,300 deaths recorded, with a death rate of 4.8 per thousand inhabitants. These results highlight the need for targeted interventions to address population health issues and promote well-being in the region.Highlights: Shifting demographics: Analyzing changes in the age and sex structure of the population in Surkhandarya region. Disease patterns: Examining the most common diseases observed, particularly those related to the circulatory and respiratory systems. Implications for population health: Assessing the impact of demographic factors and disease patterns on the overall health and well-being of the region's population. Keywords: Demographics, Population health, Surkhandarya region, Disease patterns, Mortality rates